ALLERGIES (Homoeopathy for All, 2021)
An allergic reaction occurs when a person's immune system becomes hypersensitive to certain substances, such as foods, pollen, medications, or bee venom. A substance that causes an allergic reaction is called an allergen. Many allergens are everyday substances that are harmless to most people. However, anything can be an allergen if the immune system has a specific type of adverse reaction to it.The first time a person is exposed to an allergen, they do not usually experience a reaction. It often takes time for the immune system to build up sensitivity to the substance. In time, the immune system learns to recognize and remember the allergen. As it does so, it starts making antibodies to attack it when exposure occurs. This buildup is called sensitization. The most common allergic conditions include hay fever (allergic rhinitis), asthma, allergic eyes (allergic conjunctivitis), allergic eczema, hives (urticaria),and allergic shock (also called anaphylaxis and anaphylactic shock).
Keywords: medications; allergen; allergic shock